The external and internal structures of Amphizoa davidi Lucas (Coleoptera, Amphizoidae), using X-ray phase contrast microtomography - Li, Dee; Zhang, Kai; Li, Xiaoyan; Zhu, Peiping; Xu, Caifeng; Wu, Ziyu; Zhou, Hongzhang (Zootaxa, 2015)
The Chinese endemic water beetle Amphizoa davidi Lucas, is a rare and endangered species belonging to the monotypic family Amphizoidae (Coleoptera: Adephaga). A study of the external and internal structures of A. davidi is here presented, by using X-ray phase contrast tomography and light microscopy. Morphological details and three dimensional (3D) structures of this species are provided: skeletons, muscles, reproductive organs of male and female, nervous system, alimentary canal and pygidial gland. The reproductive organs of females are compared in two different developmental phases (ages): before copulation without mature ovaries and after copulation with mature ovaries. Such detailed 3D tomographic study based on micro-CT technology may promote our understanding of the detailed morphology in Amphizoidae and Coleoptera in general.